1966
DOI: 10.1042/bj0980770
|View full text |Cite
|
Sign up to set email alerts
|

The comparative metabolism of 2,6-dichlorothiobenzamide (Prefix) and 2,6-dichlorobenzonitrile in the dog and rat

Abstract: 1. A single oral dose of either [(14)C]Prefix or 2,6-dichlorobenzo[(14)C]nitrile to rats is almost entirely eliminated in 4 days: 84.8-100.5% of (14)C from [(14)C]Prefix is excreted, 67.3-79.7% in the urine, and 85.8-97.2% of (14)C from 2,6-dichlorobenzo-[(14)C]nitrile is excreted, 72.3-80.7% in the urine. Only 0.37+/-0.03% of the dose of [(14)C]Prefix and 0.25+/-0.03% of the dose of 2,6-dichlorobenzo[(14)C]nitrile are present in the carcass plus viscera after removal of the gut. Rats do not show sex differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1966
1966
1994
1994

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 17 publications
(20 reference statements)
1
13
0
Order By: Relevance
“…In general, our results agree qualitatively with those published by Griffiths, Moss, Rose & Hathway (1966). In their study the presence of two additional metabolites of 2,6-dichlorobenzonitrile, containing sulphur amino acid residues, was demonstrated.…”
Section: Discussionsupporting
confidence: 93%
“…In general, our results agree qualitatively with those published by Griffiths, Moss, Rose & Hathway (1966). In their study the presence of two additional metabolites of 2,6-dichlorobenzonitrile, containing sulphur amino acid residues, was demonstrated.…”
Section: Discussionsupporting
confidence: 93%
“…In the urine of both rats and rabbits, conjugates of 3-and 4-hydroxy-2,6-dichlorobenzonitriles could be identified as the major metabolites. Griffiths et al (.1966) found that after administration of a small dose to rats, 41 "7 ~o and 4.0% of the radioactivity excreted in the urine was in the form of the 3-hydroxy and 4-hydroxy derivatives respectively (of a total recovery of 81%). Wit & van Genderen (1966a), using higher doses, obtained a recovery in rats of 22°,o of the dose in the form of the 3-hydroxy and 9 , %0 as the 4-hydroxy derivative.…”
Section: Metabolismmentioning
confidence: 98%
“…The metabolism of dichlobenil was studied in dogs, rats and rabbits with ~4C-labelled preparations (Griffiths, Moss, Rose & Hathway, 1966;Wit & van Genderen, 1966a). The radioactivity was almost entirely eliminated within 4 days, mainly as more polar metabolites in the urine.…”
Section: Metabolismmentioning
confidence: 99%
“…as methyl derivatives (mass spectra not shown). These are assumed to be 3and 4-hydroxy-DCB formed by rearrangement of the 3,4-epoxide Structures assigned to the metabolites isolated from urine and bile from rats dosed with as proposed by Griffiths et al (1966) in the metabolism of 2,6-dichlorobenzonitrile.…”
Section: Characterization Of Metabolitesmentioning
confidence: 99%